Embryonic Stem Cell‐Derived Mesenchymal Stem Cells (MSCs) Have a Superior Neuroprotective Capacity Over Fetal MSCs in the Hypoxic‐Ischemic Mouse Brain. (28th February 2018) - Hawkins, Kate E.; Corcelli, Michelangelo; Dowding, Kate; Ranzoni, Anna M.; Vlahova, Filipa; Hau, Kwan‐Leong; Hunjan, Avina; Peebles, Donald; Gressens, Pierre; Hagberg, Henrik; de Coppi, Paolo; Hristova, Mariya; et al.
Abstract: Human mesenchymal stem cells (MSCs) have huge potential for regenerative medicine. In particular, the use of pluripotent stem cell‐derived mesenchymal stem cells (PSC‐MSCs) overcomes the hurdle of replicative senescence associated with the in vitro expansion of primary cells and has increased therapeutic benefits in comparison to the use of various adult sources of MSCs in a wide range of animal disease models. On the other hand, fetal MSCs exhibit faster growth kinetics and possess longer telomeres and a wider differentiation potential than adult MSCs. Here, for the first time, we compare the therapeutic potential of PSC‐MSCs (ES‐MSCs from embryonic stem cells) to fetal MSCs (AF‐MSCs from the amniotic fluid), demonstrating that ES‐MSCs have a superior neuroprotective potential over AF‐MSCs in the mouse brain following hypoxia‐ischemia. Further, we demonstrate that nuclear factor (NF)‐κB‐stimulated interleukin (IL)‐13 production contributes to an increased in vitro anti‐inflammatory potential of ES‐MSC‐conditioned medium (CM) over AF‐MSC‐CM, thus suggesting a potential mechanism for this observation. Moreover, we show that induced pluripotent stem cell‐derived MSCs (iMSCs) exhibit many similarities to ES‐MSCs, including enhanced NF‐κB signaling and IL‐13 production in comparison to AF‐MSCs. Future studies should assess whether iMSCs also exhibit similar neuroprotective potential to ES‐MSCs, thus presenting a potential strategy to overcome the ethical issues associated with the use of embryonic stem cells and providing a potential source of cells for autologous use against neonatal hypoxic‐ischemic encephalopathy in humans. Stem Cells Translational Medicine 2018;7:439–449 Abstract : We hypothesize that the increased nuclear factor (NF)‐κB activation and, therefore, higher levels of interleukin (IL)‐13 production observed in pluripotent stem cell‐derived mesenchymal stem cells contributes to the increased anti‐inflammatory potential of these cells compared with other types of mesenchymal stem cells.